Compound Biejia-Ruangan tablet as an adjunctive therapy to entecavir for chronic hepatitis B complicated with hepatic fibrosis: A systematic review and meta-analysis of randomized controlled trials. Issue 32 (12th August 2022) - Xu, Yong-hong; Xue, Chuan
Abstract : Background: The compound Biejia-Ruangan tablet (CBRT), as an adjunctive therapy to entecavir, is a potential treatment for hepatic fibrosis (HF) in patients with chronic hepatitis B (HBV). However, the present study yielded inconsistent results. In this systematic review and meta-analysis, we comprehensively investigated the efficacy and safety of CBRT as an adjunctive modality to entecavir for the treatment of HBV infection complicated with HF. Methods: We searched the Cochrane Library, PubMed, Embase, CNKI, VIP, CBM, and Wangfang databases through April 1, 2022, for randomized controlled trials (RCTs) assessing the effect and safety of CBRT as an adjunctive modality to entecavir for HBV complicated with HF. The primary outcomes were biochemical parameters of serum hyaluronic acid, laminin (LN), pretype-III collagen (PC-III), and type IV collagen (IV-C). The secondary outcomes were liver function indices of serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), and total bilirubin (TBiL) levels, total effect rate, and occurrence rate of adverse events. Two researchers independently conducted study selection, data extraction, and quality assessment. Statistical analysis was performed using the RevMan 5.3 software. Results: Eight RCTs involving 747 patients were included. Compared with entecavir monotherapy, CBRT as an adjunctive therapy to entecavir exerted more encouraging effect in serum levels of hyaluronic acid (mean difference [MD] = –28.15; 95% confidence interval [CI]: –43.82 to –12.47; P < .001), LN (MD = –29.46; 95% CI: –50.69 to –8.23; P < .001), PC-III (MD = –11.83; 95% CI: –19.43 to –4.23; P < .001), and IV-C (MD = –19.62; 95% CI: –29.76 to –9.49; P < .001); levels of serum ALT (MD = –16.83; 95% CI: –26.30 to –7.36; P < .001), AST (MD = –20.52; 95% CI: –33.11 to –7.93; P < .001), and TBiL (MD = –7.54; 95% CI: –11.58 to –3.49; P < .001); and total effect rate (odds ratio = 3.53; 95% CI: 1.71–7.29; P < .001). Meta-analysis results also showed that CBRT as an adjunctive therapy to entecavir had a lower occurrence rate of adverse events (odds ratio = 0.54; 95% CI: 0.22–1.34; P < .001) than entecavir alone. Conclusion: The results of this study showed that CBRT as an adjunctive modality to entecavir may benefit HBV patients complicated with HF. High-quality RCTs are needed to confirm the current findings in the future.